2015
DOI: 10.1039/c5ra10243j
|View full text |Cite
|
Sign up to set email alerts
|

Green extraction methods and environmental applications of carotenoids-a review

Abstract: This review covers and discusses various aspects of carotenoids including their chemistry, classification, biosynthesis, extraction methods (conventional and non-conventional), analytical techniques and biological roles in living beings. Carotenoids play a very crucial role in human health through foods, cosmetics, nutraceuticals and pharmaceuticals. Among carotenoids, lycopene acts as best antioxidant.Various extraction methods have been employed for extraction of carotenoids: solvent extraction, soxhlet extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 333 publications
(395 reference statements)
0
52
1
6
Order By: Relevance
“…El b-caroteno es un compuesto carotenoide presente en la zanahoria (Daucus carota L.) con alto valor comercial y presenta un crecimiento en el mercado global por sus numerosas aplicaciones en la industria farmacéutica, alimentaria y cosmética, de igual forma, por sus beneficios en la salud. El b-caroteno juega un rol muy importante en la prevención de enfermedades del sistema inmune y otras enfermedades, como el cáncer de mama, próstata, colorectal y de pulmón; asimismo, para el tratamiento de la osteoporosis, desórdenes cardiovasculares, salud visual y problemas de sensibilidad en la piel (Singh;Ahmad, 2015).…”
Section: Discusión De Resultadosunclassified
“…El b-caroteno es un compuesto carotenoide presente en la zanahoria (Daucus carota L.) con alto valor comercial y presenta un crecimiento en el mercado global por sus numerosas aplicaciones en la industria farmacéutica, alimentaria y cosmética, de igual forma, por sus beneficios en la salud. El b-caroteno juega un rol muy importante en la prevención de enfermedades del sistema inmune y otras enfermedades, como el cáncer de mama, próstata, colorectal y de pulmón; asimismo, para el tratamiento de la osteoporosis, desórdenes cardiovasculares, salud visual y problemas de sensibilidad en la piel (Singh;Ahmad, 2015).…”
Section: Discusión De Resultadosunclassified
“…Additionally, it has also been reported that these pigments activate the cell communication and immune system (Singh et al, 2015).…”
Section: He Alth B Enefits and N Utritive Value S Of C Arotenoidsmentioning
confidence: 97%
“…Lycopene can also reduce the risk of cancer, including ovarian, breast, prostate, cervical and liver cancer. (Singh et al, 2015). On the other hand, Giovannucci et al (1995) found that higher concentration of lycopene effectively reduce the chances of cardiovascular diseases.…”
Section: He Alth B Enefits and N Utritive Value S Of C Arotenoidsmentioning
confidence: 99%
“…Several methods have been applied for extraction and analysis of carotenoids in plant tissues, and there is no generally accepted standard method for carotenoid extraction in laboratories. [85][86][87][88] Most extraction methods follow a common path involving release of the desired components from their matrices by disrupting the plant tissue, followed by removal of any unwanted components. Chloroform is more suitable than hexane, light petroleum (boiling point 40-60 C), diethyl ether, or ethyl acetate as the extraction solvent, and can efficiently extract a broad range of carotenoids.…”
Section: Analysis Of Metabolites Involved In the Formation Of Carotenmentioning
confidence: 99%